Conversion of plastic waste into fuel oil using zeolite catalysts in a bench-scale pyrolysis reactor. Issue 13 (8th March 2022) - Sivagami, Krishnasamy; Kumar, Keshav V.; Tamizhdurai, Perumal; Govindarajan, Dhivakar; Kumar, Madhiyazhagan; Nambi, Indumathi
Abstract : Catalytic pyrolysis of mixed plastic waste to fuel oil experiment was tested with ZSM-5 zeolite (commercial and synthesized) catalysts along with other catalysts. Abstract : Catalytic pyrolysis of mixed plastic waste to fuel oil experiment was tested with ZSM-5 zeolite (commercial and synthesized) catalysts along with other catalysts. The ZSM-5 zeolite catalyst was effectively produced using a hydrothermal technique via metakaolin as an alumina source. The catalytic pyrolysis of different types of plastic (single and multilayer) wastes in the presence of various catalysts was tested with a bench-scale pyrolysis setup with 2 kg per batch capacity. Polyolefin based plastics (low-density polyethylene, high-density polyethylene, and polypropylene), multilayer plastics such as biaxial oriented polypropylene (BOPP), metalized biaxial oriented polypropylene layers (MET BOPP), polyethylene terephthalate (PET), metalized polyethylene terephthalate (MET/PET), polyethylene terephthalate combined polyethylene (PET/PE), and mixed plastic waste collected from the corporation sorting center were pyrolyzed in a batch pyrolysis system with 1 kg feed to determine the oil, gas and char distributions. The performances of commercial ZSM-5 and lab synthesized ZSM-5 catalysts were compared for the pyrolysis of non-recyclable plastic wastes. Other commercial catalysts including mordenite and gamma alumina were also tested for pyrolysis experiments. The gross calorific value of oil obtained from different combinations of multilayer packaging waste varied between 10 789–7156 kcal kg −1 . BOPP-based plastic waste gave higher oil yield and calorific value than PET-based plastic waste. Sulfur content present in the oil from different plastic wastes was measured below the detection limit. The synthesized ZSM-5 zeolite catalyst produced a maximum oil output of 70% and corresponding gas and char of 16% and 14% for LDPE plastic. The strong acidic properties and microporous crystalline structure of the synthesized ZSM-5 catalyst enables increased cracking and isomerization, leading to an increased breakup of larger molecules to smaller molecules forming more oil yield in the pyrolysis experiments. Residual char analysis showed the maximum percentage of carbon with heavy metal concentrations (mg kg −1 ) in the range of viz., chromium (15.36–97.48), aluminium (1.03–2.54), cobalt (1.0–5.85), copper (115.37–213.59), lead (89.12–217.3), and nickel (21.05–175.41), respectively.